Quality and job security at the Autonomous University of Coahuila in a pandemic context - Barboza Lara, Cesar Rolando (2023)
Occupational safety and quality are two essential pillars within any organization today, since these factors are responsible for safeguarding the integrity of the collaborators within the same, in addition to providing a full and dignified working life so that workers can have an efficient professional development. The general objective of the research is to determine the level of knowledge of the concept of quality and occupational safety that the staff of the higher level schools and faculties belonging to the Autonomous University of Coahuila in the city of Monclova, Mexico has in a context of pandemic, studying the teaching, administrative and manual population of these institutions. A descriptive, non-experimental, cross-sectional research was carried out. A population of 169 people belonging to the schools and faculties of the UAdeC in Monclova was surveyed, where 93.5% were found to have a positive level of knowledge about the concept of occupational safety, while the remaining 6.5% were found to have a negative level. The institutions studied have a good culture of safety and work quality, providing their members with the necessary instruments for physical care and well-being.